2018
DOI: 10.4066/biomedicalresearch.29-18-665
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of Jatropha tanjorensis leaves and effects of its aqueous extract on carbon tetrachloride induced oxidative stress in male Wistar albino rats

Abstract: Many consumers of Jatropha tanjorensis leaves claim that the leaves are nutritious and in addition, possess nutraceutical properties that promote good health. Such claims can be misleading since there is no scientific data to validate their claims. This study evaluated the nutritional and antioxidant properties of the aqueous extract of Jatropha tanjorensis leaves in carbon tetrachloride induced male Wistar albino rats with the aim of validating some nutritional and nutraceutical properties claimed by local co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…In addition, there were numerous mineral elements abundant in jatropha leaves which accelerate metabolic processes and promote growth and development (Bello et al, 2008). On the other hand, the levels of essential amino acids in jatropha leaves were lower compared to those in other plants (Makkar et al, 1998) which agreed with the findings of this research and in contrast to the findings of (Chigozie et al, 2018) who observed that Jatropha tanjorensis leaves were abundant in essential amino acids.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, there were numerous mineral elements abundant in jatropha leaves which accelerate metabolic processes and promote growth and development (Bello et al, 2008). On the other hand, the levels of essential amino acids in jatropha leaves were lower compared to those in other plants (Makkar et al, 1998) which agreed with the findings of this research and in contrast to the findings of (Chigozie et al, 2018) who observed that Jatropha tanjorensis leaves were abundant in essential amino acids.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, jatropha leaves have the greatest magnesium content, which is essential for the production of DNA and RNA during cell division Sanderson et al (2013). Other determinations done by Chigozie et al (2018) recorded that jatropha leaves are rich in vitamin A, deficient in vitamins B1, C and vitamin E. Moreover, allelopathic effects may be found in plants and microbes, although in vegetables they are stronger. The allelopathic effect is a natural intervention in which a plant creates chemicals and metabolites that, when released, may be beneficial or detrimental to other plants/organisms Rejilia and Vijaykumar (2011), (Mongelli et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Phytochemical screening analysis revealed the presence of tannins, phlobatannins, saponins, terpenoids, glycosides, and alkaloids in the plantextract. Elsewhere it is reported that tannins, alkaloids, saponins, flavonoids, and glycosides could be associated with the antimicrobial activities of someplants [23,24]. The antibacterial activities of these plants may reside in these active principles as noted by [25].…”
Section: Table 2: Antimicrobial Activity Of Extracts Of Vernonia Amyg...mentioning
confidence: 98%
“…aureus= Staphylococcus aureus, Esch. coli = Escherichia coli DISCUSSION Medicinal plants are used by a large proportion of developing nations [20][21][22][23][24][25][26][27][28][29][30]. The reason for this may be a true improvement in disease conditions after herbal treatment [31][32][33][34][35][36][37][38][39][40].…”
Section: Table 2: Antimicrobial Activity Of Extracts Of Vernonia Amyg...mentioning
confidence: 99%
“…Petioles are 12-19 cm long (Akhilesh & Tewari, 2015). Jatropha tanjorensis Common Names: Catholic vegetable, Lapalapa or Iyana-Ipaja (Yoruba), Ugu-Oyibo (Igbo), "hospital too far" (Pidgin English) (Ochulor, Njoku, Uroko & Egba, 2018).…”
Section: Jatropha Tanjorensis Jatropha Tanjorensis Plant Description ...mentioning
confidence: 99%